A new method of producing high strength oil palm shell lightweight concrete - Shafigh, Payam; Jumaat, Mohd Zamin; Mahmud, Hilmi; Alengaram, Ubagaram Johnson (Elsevier, 2011)
This paper presents a new method to produce high strength lightweight aggregate concrete (HSLWAC) using an agricultural solid waste, namely oil palm shell (OPS). This method is based on crushing large old OPS. Crushed OPS are hard and have a strong physical bond with hydrated cement paste. The 28 and 56. days compressive strength achieved in this study were about 53 and 56. MPa, respectively. Furthermore, it was observed that it was possible to produce grade 30 OPS concrete without the addition of any cementitious materials. Compared to previous studies, significantly lower cement content was used to produce this grade of concrete. Unlike OPS concrete incorporating uncrushed OPS aggregate, this study found that there is a strong correlation between the short term and 28-day compressive strength.